Pogostnost bakterijske vaginoze in povezava s prezgodnjim porodom - Novak, Mojca (Medicinski razgledi, 1998)
Bacterial vaginosis is characterized by the presence of large amounts of anaerobic bacteria, Gardnerella vaginalis and Mycoplasma hominis in the vagina, where they replace the normally present lactobacilli. The condition isimplicated as a possible cause of preterm delivery. In our study, bacterial vaginosis was diagnosed clinically and microbiologically. The incidence of bacterial vaginosis in 72 pregnant women attending the Clinic for Pathologic Pregnancy (5,5%) was lower than that in 100 women examined prior to artificalabortion at the Day Clinic (14%) and in 23 women evaluated at the Clinic for Sexually Transmitted Diseases (23,0%). The diference in incidence between the groups was not statistically significant. Factors found to be significantly associated with bacterial vaginosis included: smoking 15 or morecigarettes per day (odds ratio 7,15; 95% contidence interval 1,9-26,0) andage < 17 years at the first sexual intercourse (odds ratio 3,64;95% contidence interval 2,2-7,1). The incidence of bacterial vaginosis is higher among non-pregnant women than among pregnant ones (odds ratio 3,22;95% contidence interval 1,5-6,8), and in the first and second trimester of pregnancy than in the third (odds ratio 2,22; 95% contidence interval 0,9-5,2). Sexual habits and cigarette smoking seem to predisponse women to bacterial vaginosis. The condition may resolve spontaneously during pregnancy.The pH determination and amine odour of the vaginal discharge can beused as a reliable screening test, while Gram-stain reading of the vaginal smear is employed to corroborate the diagnosis. Because of the small size of the series studied, it was not possible to profe the relationship between bacterial vaginosis and preterm delivery.
Keywords: ginekologija; Vaginosis, bacterial; Risk factors; nožnice; Labor, premature; bakterijske infekcije; Hydrogen-ion concentration; prezgodnji porodi; Vaginal smears; Gardnerella vaginalis; Mycoplasma hominis